PEMBINAAN GAYA KEPEMIMPINAN DAN KOMUNIKASI EFEKTIF PADA PADA SISWA DAN SISWI SMA ANANDA KOTA BATAM - Michael Jibrael Rorong; Zuhdi Arman; Dedi Epriadi (PUAN INDONESIA, 2022)
Students and Students are a place for students' aspirations to express their creativity. OSIS is formed based on the decision of the principal of the school which has a management body. Students who are involved in the OSIS management body must pass several criteria and requirements, including having communication skills and having a leadership spirit. Communication has a strong influence in shaping a person's attitude and leadership style in an organization. Students must be given briefings on attitudes and leadership styles so that they can direct, control their members and be responsible so that all parts of the work are coordinated in order to achieve company or organizational goals. One of the requirements to become an OSIS administrator is sitting at Ananda High School in Batam City, where the psychological condition of students is still unstable to lead. So that there are some conflicts that arise such as misunderstanding between members, task structure factors and organizational structures, for example, the unequal desire between the treasurer and chairman, personal factors, namely individuals must make decisions concerning themselves and the organization, environmental factors such as the absence of support from the environment or certain parties, differences of opinion, incomplete gatherings, many administrators who leave, there is leisure between members, poor time management and declining performance.